2008
DOI: 10.1007/s10260-008-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing several exponential populations with more than one control

Abstract: Simultaneous confidence intervals, Multiple comparisons, Critical points, Numerical integration, Pareto distribution,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…when the scale parameters are equal or unequal. For example, see Ng et al [6], Wu and Chen [7][8], Wu and Wu [9], Lam and Ng [10], Singh and Abebe [11], Wu et al [12], and Maurya et al [4]. Most of these researchers used Lam's [13][14] technique to construct SCIs.…”
Section: Introductionmentioning
confidence: 95%
“…when the scale parameters are equal or unequal. For example, see Ng et al [6], Wu and Chen [7][8], Wu and Wu [9], Lam and Ng [10], Singh and Abebe [11], Wu et al [12], and Maurya et al [4]. Most of these researchers used Lam's [13][14] technique to construct SCIs.…”
Section: Introductionmentioning
confidence: 95%
“…Ahmadi and MirMostafaee [1] examined the prediction intervals for future order statistics and records data where the underlying distribution is twoparameter exponential. Singh and Abebe [20] compared multiple exponential populations with more than one control. Kao [10] showed that the amount of current needed to break an insulator of the P-type high-voltage metal oxide semiconductor (MOS) transistor (HPM) on a non-volatile drive memory wafer follows the two-parameter exponential distribution and this article nicely demonstrates the importance of the two-parameter exponential distribution in the engineering sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Under two-stage sampling scheme or the homogeneity assumption of scale parameters, the problem of comparing exponential location parameters with a control or controls has been addressed by several authors; e.g. [8] , [13] and [14]. Recently, Wu et al [15] proposed conservative two-sided and one-sided SCIs for θ i − µ 1 , i = 1, .…”
Section: Introductionmentioning
confidence: 99%